A novel ethical analysis of educational XR and AI in literature - Bahar Memarian; Tenzin Doleck (Computers & Education: X Reality, 2024)
This review paper aims to search the landscape of Extended Reality or XReality technology in light of Artificial Intelligence or AI. Through an examination of the Web of Science or WoS, a total of 29 studies were selected for review. We extracted information on the XReality with AI trends in the studies and further classified the pedagogical impact of the studies using the E3XReality framework suggesting that XReality technology may fall into three levels (three Es for XR hence E3XR): 1) Ethics (making sure we do and receive no harm in learning), 2) Educational effectiveness (making sure learning is effective to our goals and outcomes), and 3) Eudaimonia (making sure learning is both effective and ethical). Using open and axial coding, we find that a survey of perceptions or review of the literature was most often made, followed by the study of technical and pedagogical interventions. VR followed by MR was noted the most in the reviewed studies and surprisingly no mention of AR in the silo was made. The use of AI with XReality was mostly done to provide actionable insight, followed by insight and control. The analysis of studies against the conceptual framework E3XReality suggested that current work is largely at the education state and more work is needed to transition to a more sophisticated state of Eudaimonia. Further, several challenges were obtained from the 29 reviewed studies. The contribution of this paper is to offer an extensive synthesis of challenges as well as future recommendations for using XReality with AI in education.